Tianjin Medical University General Hospital - H. Li; X. Li; X. Song; W. Tian; A. Fan; Ch. Han; H. Zhang; F. Xue; Y. Wang (Акушерство, гинекология и репродукция, 2025)
With over 70 years of development, the Department of Obstetrics and Gynecology at Tianjin Medical University General Hospital has evolved into a comprehensive center for clinical care, research, and education, showcasing significant influence and technical strength in the field of obstetrics and gynecology. The department operates more than 200 beds, handles over 260,000 outpatient and emergency visits annually, and performs nearly 10,000 surgeries each year. As the final referral and rescue center for complex and critical cases in Tianjin, the department excels in sub-specialties such as perinatal medicine, gynecologic oncology, obstetric critical care, reproductive medicine, and gynecological endocrinology. It has made significant advances in precision diagnosis and personalized treatments, leading the development of the discipline in Northern China. In recent years, the department has demonstrated outstanding scientific innovation, undertaking numerous national and provincial-level projects, publishing high-impact papers, and contributing to multiple international and national guidelines. The department continues to advance both academic and clinical excellence, significantly contributing to the Healthy Tianjin Initiative and the broader Healthy China Action.